Media representation of political leadership and governance in South Africa: press coverage of Jacob Zuma - Nkomo, Sibusiso (My University, 2017)
This research report examines news media representation of political leadership and governance in South Africa between 2007 and 2013, when President Jacob Zuma served his first terms as ANC leader and later as the head of state. The research sought to find out what themes and ideas exist about political leadership in news media more than 20 years since the advent of democracy. Quantitative manifest content analysis is utilised to analyse newspaper articles from the City Press, Mail & Guardian, the Sunday Independent and the Sunday Times. The results show that media representation of political leadership is most discussed in opinion articles and editorials and relies on key democratic concepts such as freedom of expression and freedom of the media. The key themes and ideas that emerge include the personalisation of leadership, defining leadership, debate on how to lead, Zuma’s own leadership traits versus expectations and it became clear that news media evaluated Zuma as head of state or leader of the nation more often than as president of his party.
A research report submitted to the School of Literature, Language and Media in the Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Journalism and Media Studies by combination of coursework and research, Johannesburg, 2016
Keywords: Zuma, Jacob; Mass media--South Africa; Journalism--South Africa; Political leadership--South Africa; South Africa--Politics and government--21st century